The Effect of Working Capital Turnover, Sales Growth, and Import Exemption Facilities of Export Destinations (KITE) on The ROA of Manufacturing Companies - B. Andreas Mada; Arif Ginanjar (Perbanas Institute, 2022)
The purpose of this study is to analyse the effect of working capital turnover, sales growth, and KITE exemption facility to Return on Asset (ROA) of manufacturing companies that receive import tax exemption facility (KITE) in 2020. There were 42 companies used as the sample. The data used in this study was obtained from annual financial reports of manufacturing companies in 2020 that submitted to Directorate General Customs and Excise Indonesia. The analysis technique used in this study is cross section regression. The result of this study found that both working capital turnover, sales growth, and KITE exemption facility show no effect on Return on Asset (ROA).